Student perception and usage of an automated programming assessment tool. - Rubio-Sánchez, Manuel; Kinnunen, Päivi; Pareja-Flores, Cristóbal; Velázquez-Iturbide, Ángel (Computers in Human Behavior, 2014)
Highlights: [•] We empirical evaluate Mooshak, an automated computer programming assessment system. [•] We provide a highly detailed analysis of student usage of Mooshak. [•] The usage of Mooshak was adequate in relation to students’ own testing. [•] Mooshak’s feedback should be richer to improve its acceptance among students. [•] We found no statistical evidence to claim Mooshak reduced the dropout rate.